Role Stress and Prosocial Service Behavior of Hotel Employees: A Moderated Mediation Model of Job Satisfaction and Social Support - Jin, Yixing; Cheng, Lin; Li, Ying; Wang, Yingda (Frontiers in Psychology, 2021)
Since hotel employees’ positive behavior is prone to increase customer satisfaction, it is critical to explore the influencing mechanism of role stress on prosocial service behavior to relieve their stress and improve service quality and hotel performance. This study aims to develop and test a moderated mediation model that links hotel employees’ role stress to prosocial service behavior. Based on the conservation of resources theory and job demands-resources model, this study suggests that the effect of role stress on prosocial service behavior is mediated by the level of job satisfaction, whereas the relationship between role stress and job satisfaction is moderated by social support. Data from 256 hotel employees in China largely support our hypotheses that role stress reduces job satisfaction, and that job dissatisfaction is related to low levels of prosocial service behavior. Furthermore, the data show that job satisfaction partly mediates the relationship between role stress and prosocial service behavior, and social support weakens the relationship between role stress and job satisfaction. The results help us to understand the role of organization-level resources in the workplace and how role stress and job satisfaction influence prosocial service behavior.